Assessment of Carbonate Rocks, Western Desert of Iraq as Dimension Stones for Building - Fadhil, Linaz Anis; Awadh, Salih Muhammad (Arab Journal for Sciences and Research Publishing, 2022)
The current study aimed to assess the Carbonate rocks as dimension stones for building. Carbonate rocks collected from the Mauddud Formation (Albian- Cenomanian), within the Western Desert of Iraq are studied petrographically, mineralogically and geochemically. Physical and mechanical properties of selected samples are found to assess their suitability as building stones. Field work is carried out and evaluated sampling of three sites of carbonate rocks. Petrography and mineralogy of these rocks are studied using polarized microscope and XRD technique.Three microfacies (peloidal wackstone-packstone, peloidal packstone and crystalline carbonate) are distinguished. Dolomitization, cementation and recrystallization are themain diagenetic processaffecting the physical and chemical properties of them. Dolomite is the predominant mineral in the 1M and 2M sites, whereas calcite is the most predominant mineral in the 3M site, so it is classified as limestone. Chemically samples are analyzedfor SiO2, Al2O3, CaO, MgO, Fe2O3, Na2O, K2O, TiO2, MnO and LOI. CaO and MgO are the most predominant oxides confirming the abundance of calcite and dolomiteso it is classified as a calcitic dolomite for 1M and 2M sites while classified as limestone for 3M site. The results of analysis physical and mechanical properties (bulk density, water absorption, compressive strength, modulus of rupture and abrasion resistance) are indicate that selected rocks are suitable as dimension stones for building according to American Standard for Testing Materials (ASTM) specification.
Keywords: Carbonate rocks; Dimension stones; Western Desert of Iraq; Physical and mechanical properties; mechanical; Physical; ASTM